Adalékok a régiótörténeti kutatásokhoz 2. : Kárpátalja visszatérésének diplomáciai előkészítése, különös tekintettel Teleki Pál földrajzi/gazdasági érveire - Gulyás, László (Közép-Európai Közlemények, 2016)
On 16th February 1939 Governor Miklós Horthy nominated Pal Teleki as prime minister. In the focus foreign policy of Teleki was the question of Subcarpathia. For answering of the question why Subcarpathia belongs to Hungary, the Hungarian diplomacy worked out a system of arguments compared three elements.First point of this system was the historical arguments. Summary of it in one sentence: the „natio fidelissima” (the most faithfully nation), the Ruthen lived within Hungarian nation during 1000 years, so this status has to be set back.The second part was the political arguments: Czechoslovak politicians promised in 1918-1920 in Versailles, that this area will get autonomy, but this decision was postponed for 20 years, and when they got it, it happened under pressure. The Hungarian government will give real working autonomy for Subcarpathia. The third part of reasons was geographical argument. We will present these in details in our study.